"I haven't come a long way, and I'm not a baby": Task assignment and diversity of the Supreme Court bar. (16th November 2021) - Szmer, John; Kaheny, Erin B.; Sarver, Tammy A.
Abstract: Objective: Gender disparities in litigation task assignment are not limited to the trial court context; they are present in even the highest of courts in the United States. We explore and seek to explain the gendered patterns of participation by lawyers arguing before the U.S. Supreme Court. Methods: After quantitatively describing participation by female attorneys in Supreme Court litigation, we use logistic regression and fractional logit, respectively, to identify factors that influence the degree to which women deliver oral arguments and participate in writing litigant briefs. Results: Descriptively, we find that male attorneys present more oral arguments than female attorneys, and most litigant briefs are written by male‐dominated teams. In fact, more than a third of the briefs are only signed by men. In multivariate analyses of Supreme Court oral arguments and briefs, we find that women are more likely to argue and sign briefs on issues in which they are stereotypically perceived as more competent (women's issues) and less likely to participate in issue areas where they are perceived to be less competent, like economic issues. Similarly, women are less likely to orally argue in complex cases. Conclusion: While occupational segregation and other factors may play a role, the participation of female attorneys in this forum is likely driven, in part, by stereotyped assessments of their competency.